Exploring Social Support for Women Coping with a Cardiac Rehabilitation Programme after Acute Coronary Syndrome: A Systematic Review of Qualitative Studies - Sukhbeer Kaur, Darsin Singh; Abqariyah Binti Yahya, Ahmad Noor; Fatimah, Binti Ahmedy; Khatijah Lim, Abdullah *; Imran, Zainal Abidin; Anwar, Bin Suhaimi; Sator, Patricia (Medical Journals Sweden AB, 2022)
Objective: Female sex is a major barrier to completing a programme of cardiac rehabilitation (CR) after acute coronary syndrome (ACS). Women require significant social support to promote compliance and the ability to cope with CR programme attendance. The aim of this systematic review of qualitative studies was to explore social support among women coping with CR programme attendance at phase II CRP is 3 months after their cardiac event.